Editorial, Volume 7, Issue 1 - Kristy L Archuleta (Journal of Financial Therapy, 2016)
The Journal of Financial Therapy would not exist without the time and efforts of our excellent reviewers. You may be asking, “what does a reviewer do?” JFT is a unique scholarly publication because papers require the rigor of academic standards, but also must be translatable to non-researchers. It is not uncommon for researchers and practitioners to fail to communicate effectively with one another because the two groups speak what seems like different languages. Therefore, it is the goal of JFT to publish quality scholarly research and to emphasize the practicality of the research.
Keywords: editorial; financial therapy; Journal of Financial Therapy; peer review